Analysis of The Utilization of Audio-Visual Media as a Basic Study of Control System Integration for Science Learning - Radeswandri, Radeswandri; Yovita, Yovita; Syafaren, Alaniyah; Gafur, Irfan Andi (Journal of Natural Science and Integration, 2023)
This study aimed to carry out a literature review analysis on the application of learning science used technology, the usefulness of teaching media, and obstacles to the implementation of educational technology. This study used a cross-sectional survey design with a total sample of 116 people consisting of lecturers, educators, and students (student teachers). The data collection technique included an online questionnaire consisting of multiple-choice questions and a brief description of the implementation of disruptive technology. The data obtained were analyzed descriptively qualitatively and the indicators assessed included relevance, educator ability, ease of use, availability, and usefulness. From the results of the study, it can be concluded that the utilization of visual media for learning science has been used by various Educators and Students, however, they have not been able to develop audio-visual media from the results of Industry 4.0 technology.Keyword: utilization, obstacles, industry 4.0 technology, learning science